2015
DOI: 10.1016/j.mayocp.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Environmental Exposures in the Etiology of Eosinophilic Esophagitis

Abstract: Eosinophilic esophagitis (EoE) is an emerging clinicopathologic entity defined by abnormal esophageal eosinophilic infiltration. Management of this disease is hampered by limited understanding of etiologic and controllable risk factors. The aim of this systematic review was to determine the environmental risk factors for EoE. We searched PubMed, Web of Science, and EMBASE databases from 1950 through June 30, 2015. To identify additional relevant studies, we hand searched bibliographies of included articles. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 54 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…There is intense interest in learning why the incidence and prevalence of EoE are increasing. 13, 8890 Although some genetic factors have been associated with EoE, 15 the rapid trends in EoE incidence indicate a role for environmental factors in disease risk. 14 In a study of a large administrative database in the United States, prevalence increased steadily with age, to a peak value in individuals 30–44 years old.…”
Section: Epidemiologymentioning
confidence: 99%
“…There is intense interest in learning why the incidence and prevalence of EoE are increasing. 13, 8890 Although some genetic factors have been associated with EoE, 15 the rapid trends in EoE incidence indicate a role for environmental factors in disease risk. 14 In a study of a large administrative database in the United States, prevalence increased steadily with age, to a peak value in individuals 30–44 years old.…”
Section: Epidemiologymentioning
confidence: 99%
“…There are several factors that are thought to contribute to the increase in the incidence of EoE in recent years[9]: (1) The hypothesis of hygiene and bacterial dysbiosis, that is, that modern life and hygiene conditions have decreased the incidence of infections, resulting in less bacterial exposure and thus altering the body’s microbiota and epithelial permeability[10]; (2) Environmental factors, such as changes in aeroallergen air conditions and concentrations of airborne pollen[11,12] and/or genetic and chemical modifications used in the cultivation, processing, and packaging of food[9]; (3) Decreased frequency of infection by Helicobacter pylori (H. pylori) in certain countries (it has been found that this bacterium increases Th1 and Th17 populations, downregulating Th2)[13]; (4) Gastroesophageal reflux disease (GERD), an entity that leads to the injury of intraepithelial junctions, causing greater allergen permeability in the esophageal epithelium as measured by mucosal impedance[14,15]; and (5) The use of acid-suppressive drugs, which is paradoxical, given that proton pump inhibitors (PPIs) exert an anti-inflammatory effect by blocking eotaxin secretion[16] and inhibiting acid secretion, thereby reducing activation of digestive enzymes such that the antigens in food do not degrade and the digestive system is protected from the immune response mediated by these proteins[17].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Thus, studies such as that of Moawad et al [7] and Fahey et al [8] show that there may be a correlation between the incidence of EoE and some aeroallergens, although to date it has been impossible to distinguish which ones may be responsible. A recent systematic review recognizes that seasonal, geographical, and climate-based differences in disease prevalence could be due to multiple environmental exposures, although the exact mediators of this process remain elusive [19].…”
Section: Resultsmentioning
confidence: 99%